Efficient production of hydrogen from formic acid using a Covalent Triazine Framework supported molecular catalyst. Issue 5 (11th February 2015) - Bavykina, A. V.; Goesten, M. G.; Kapteijn, F.; Makkee, M.; Gascon, J.
Abstract A heterogeneous molecular catalyst based on IrIIICp* (Cp*=pentamethylcyclopentadienyl) attached to a covalent triazine framework (CTF) is reported. It catalyses the production of hydrogen from formic acid with initial turnover frequencies (TOFs) up to 27 000 h−1 and turnover numbers (TONs) of more than one million in continuous operation. The CTF support, with a Brunauer–Emmett–Teller (BET) surface area of 1800 m2 g−1, was constructed from an optimal 2:1 ratio of biphenyl and pyridine carbonitrile building blocks. Biphenyl building blocks induce mesoporosity and, therefore, facilitate diffusion of reactants and products whereas free pyridinic sites activate formic acid towards β‐hydride elimination at the metal, rendering unprecedented rates in hydrogen production. The catalyst is air stable, produces CO‐free hydrogen, and is fully recyclable. Hydrogen production rates of more than 60 mol L−1 h−1 were obtained at high catalyst loadings of 16 wt % Ir, making it attractive towards process intensification.